Analisis Location Quotient (LQ) Dan Model Rasio Pertumbuhan (MRP) Usaha Peternakan Sapi Potong Di Provinsi Sumatera Utara - Anita Zahra; Dina Rizqa Ananda; Jantri Syahputra Pangaribuan; Zakiatun Maknun4; Kiagus Muhammad Zain Basriwijaya (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
The beef cattle farming industry plays an important role in supporting food security and national economic growth. North Sumatra Province is an area with supportive geographical potential and great opportunities for developing this sector. However, several challenges such as low productivity, market competition, and infrastructure limitations still hinder its development. This study aims to analyze the potential and comparative advantages of North Sumatra Province in the development of beef cattle farming and to predict its growth in the future. The methods used are Location Quotient (LQ) analysis and the Growth Ratio Model (MRP). The data used are secondary data from the last three years (2020-2022) obtained from the Central Bureau of Statistics (BPS) of North Sumatra Province, the Directorate General of Livestock and Animal Health, and the North Sumatra Provincial Livestock Office. LQ analysis is used to identify leading commodities in the livestock sector, while MRP is used to predict the growth of the beef cattle industry. The analysis results show that several districts in North Sumatra, such as Deli Serdang, Simalungun, and Asahan, have an LQ greater than 1, indicating that beef cattle farming is a leading sector. Meanwhile, several districts, such as Langkat and Karo, have an LQ less than 1, indicating that this sector has not yet become a base for beef cattle farming. With an MRP of 4.0%, Simalungun shows the highest growth rate, followed by Deli Serdang and Asahan. This research provides an important overview of the potential and challenges of beef cattle farming in North Sumatra Province for appropriate policy-making and the future development of this sector.